New fossil species of the extant genus Lepidobatrachus (Anura, Ceratophryidae) from the Early Pliocene of central Argentina - Nicoli, Laura (2015)
I describe a new fossil species of the extant anuran genus Lepidobatrachus from Early Pliocene sediments of central Argentina. This species was erroneously attributed to the living species L. laevis in prior studies. However, reanalysis of the fossil material demonstrated that some anatomical structures, as well as their taxonomic significance, were misinterpreted. The description and comparative analysis presented here demonstrate than this specimen represents a new fossil species of Lepidobatrachus. Although it possesses most possible synapomorphies of Lepidobatrachus, some features of the architecture of the skull of the fossil species, referring to the palatal contact of the maxilla with the surrounded bones, remember the skull of the other ceratophryid genus. Additionally, the new species differs from all ceratophryids in the absence of a supraorbital shelf. The paleoenvironmental significance of this discovery is also discussed.